A meta Analysis of Aidi Injection plus Taxotere and Cisplatin in the Treatment of Non-small Cell Lung Cancer - Quan WANG; Xiran HE; Jinhui TIAN; Xiaogang WANG; Peifan RU; Ziliang RUAN; Kehu YANG (Chinese Journal of Lung Cancer, 2010)
Background and objective Compared with chemotherapy, whether aidi injection can improve the patient's quality of life is not definite. The aim of this study is to evaluate the efficacy and safety of axotere plus eisplatin chemotherapy combining aidi injection for patients with non-small cell lung cancer (NSCLC). Methods We searched relevant randomized controlled trials (RCTs) from Cochrane library, Pubmed, EMBASE, CancerLit, VIP, CBM and CNKI etc. The search was finished in March 20, 2010. We traced the related references and experts in this field, besides we also communicated with other authors to obtain some certain information that has not been found. RCTs of aidi injection plus TP versus TP for advanced NSCLC were included. We evaluated the quality of these included studies and analyzed data by Cochrane Collaboration's RevMan 5.0 software. Results Eleven RCTs involving 800 patients were included. meta analysis results suggested that compared with TP chemotherapy alone, the combination had a statistically significant benefit in healing efficacy (RR=1.2, 95%CI: 1.10-1.47, P=0.001) and improving quality of life (QOL) (RR=1.85, 95%Cl: 1.54-2.21, P < 0.001). Besides, the combination also had a statistically significant benefit in myelosuppression, white blood cell (WBC)(RR=0.71, 95%CI: 0.57-0.87, P=0.001) and hematoblast (RR=0.59, 95%CI: 0.40-0.87, P=0.008) and in reducing the gastroenteric reaction (RR=0.75, 95%CI: 0.58-0.98, P=0.03). But the combination had no statistically significant benefit in prevention of reducing hemoglobin (Hb) (RR=0.97, 95%CI: 0.70-1.34, P=0.85), liver function (RR=0.63, 95%CI: 0.09-1.57, P=0.18), kidney function (RR=0.42, 95%CI: 0.14-1.24, P=0.12), peripheral neuritis (RR=0.86, 95%CI: 0.56-1.32, P=0.50), and baldness (RR=0.92, 95%CI: 0.63-1.34, P=0.66). Conclusion Compared with TP chemotherapy alone, the combination can significantly improve the efficiency, QOL and myelosuppression, and reduce adverse events.